2009
DOI: 10.15288/jsad.2009.70.400
|View full text |Cite
|
Sign up to set email alerts
|

A Finer Examination of the Role That Negative Affect Plays in the Relationship Between Paternal Alcoholism and the Onset of Alcohol and Marijuana Use

Abstract: ABSTRACT. Objective: This study was designed to separately examine the relations between four fundamental components of negative affect (sadness, fear, guilt, and hostility) and the onset of substance use. An additional goal was to examine the potential mediating roles that these components of negative affect play in the relationship between paternal alcoholism and the initiation of substance use. Method: The sample included 200 adolescents ages 15-19 years (62% girls; 68% white; 56% children of alcoholics [CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…A few studies, on the other hand, have found no gender differences in the relationships between NA/mood disorders and substance use (e.g. Armeli et al, 2000;Kaplow et al, 2001;Ohannessian and Hesselbrock, 2009). A larger sample of depressed young men (and women) should be examined to clarify these possibilities and to investigate whether the genders do, in fact, use substances to regulate affect differently.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies, on the other hand, have found no gender differences in the relationships between NA/mood disorders and substance use (e.g. Armeli et al, 2000;Kaplow et al, 2001;Ohannessian and Hesselbrock, 2009). A larger sample of depressed young men (and women) should be examined to clarify these possibilities and to investigate whether the genders do, in fact, use substances to regulate affect differently.…”
Section: Discussionmentioning
confidence: 98%
“…People who are high risk-takers are more likely to exhibit life-style behaviors characterized by disinhibition and loss of moderation. These behaviors include increased frequency and amount of alcohol consumption, caffeine consumption, smoking, and recreational drug use, as well as gambling and engagement in risk-taking behavior 57,58. Being a high risk-taker may then be the cause of increased alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In one sample of 200 adolescents, guilt was significantly negatively associated with the onset of regular drinking and marijuana use [54]. Shame was not examined.…”
mentioning
confidence: 99%